Low Wage Returns to Schooling in a Developing Country: Evidence from a Major Policy Reform in Turkey - Abdurrahman Aydemir; Murat G. Kirdar (Institute for the Study of Labor (IZA), 2015)
In this paper, we estimate the returns on schooling for young men and women in Turkey using the exogenous and substantial variation in schooling across birth-cohorts brought about by the 1997 reform of compulsory schooling. We estimate that among 18- to 26-year-olds, the return from an extra year of schooling is almost zero for men and 3.8 percent for women. The low level of these estimates contrasts starkly with those estimated for other developing countries. We identify several reasons why the returns on schooling are low and why they are higher for women in our context. In particular, the policy alters the schooling distributions of men and women differently, thus the average causal effect we estimate puts a higher weight on the causal effect of schooling at higher grade levels for women than for men.
Keywords: J18; J31; I21; I28; 330; returns to education; compulsory schooling laws; wages; gender